O projeto de gestão ambiental e territorial indígena (Projeto GATI): a experiência na terra indígena Oco'Y - Dias, Roberto dos Anjos (2017)
The aim of this work was to understand the application of the Indigenous Environmental and Territorial Management Project - GATI Project (GEF INDÍGENA/PNUD BRA09/G32) at Oco'y Indigenous Land. The Project is a pilot experiment that was applied in 32 indigenous lands at 05 different Brazilian biomes. This project has broad objectives that aim to consolidate Brazilian indigenous lands as essential areas of biodiversity conservation. The GATI Project lasted two years, period in which several actions were proposed and implemented at Oco'y Indigenous Land. It was an interdisciplinary research, addressing geographical, philosophical, anthropological, among others concepts. To support the analysis, a theoretical discussion about the relationship between indigenous, ethno-development, territory, Guarani agriculture, environmental conservation, sustainable development and ethics was performed. By the analysis of documents, interviews and fieldwork, it was identified that few of the planned actions were carried out in an incipient way. In addition, it was verified that the Project presented adequate theoretical presuppositions, advances in the overcoming of bureaucracies and institutional barriers; however, its application did not have community participation, institutional support as well as there was no continuity of actions.